Investigation of The Value of Spring Constant and Mass on The Efficiency of Moving Mass Devices - Taqiuddin, Muhammad Azmi; Shaharudin, Nik Mohd Ridzuan; Yaakob, Omar (International Journal of Electrical, Energy and Power System Engineering, 2022)
Simple configuration and has good efficiency, make a moving mass stabilizer one of the options that can be applied to reduce roll motion on a small vessel. This stabilizer however has a limitation in dealing with the ship’s hydrostatic changes while on duty especially when the stabilizer is designed to be passive. The purpose of this research is to improve the ability of the stabilizer to be able to adapt the change in ship hydrostatics. A Tsunami 22’ fishermen vessel model was selected to be used for this research. By conducting roll decay experiments, natural frequency data from the vessel is then used to design calculations for the device on two different load conditions. Moving mass stabilizer frequency is dependent on two parts that are the spring coefficient “k” and the weight of the mass moving. In this Research, Spring adjustment is selected to make the stabilizer able to change frequency following change on the vessel. It is found that the best frequency ratio between the frequency of stabilizer and vessel is 1. Adjusting the spring of the stabilizer turned out to give an increase in device performance by 8.9 % when compared to adjusting the mass. The results obtained in this research indicate the moving mass stabilizer has good potential to reduce the roll motion.